Microfinance poverty assessment tool - Henry, Carla; Sharma, Manohar; Lapenu, Cecile; Zeller, Manfred (Washington, D.C : The World Bank, 2003)
Business
2004-09-21
Keywords: Microfinance; Poverty; Microfinance institutions; Planning; UNDP